Crystal structure of tetraaquabis(3,5-diamino- 4H-1,2,4-triazol-1-ium)cobalt(II) bis[bis(pyridine-2,6-dicarboxylato)- cobaltate(II)] dihydrate - Johnson, Atim; Mbonu, Justina; Hussain, Zahid; Loh, Wan Sin; Fun, Hoong Kun (International Union of Crystallography, 2015)
The asymmetric unit of the title compound, [Co(C2H6N5)2- (H2O)4][Co(C7H3NO4)2]22H2O, features 1.5 CoII ions (one anionic complex and one half cationic complex) and one water molecule. In the cationic complex, the CoII atom is located on an inversion centre and is coordinated by two triazolium cations and four water molecules, adopting an octahedral geometry where the N atoms of the two triazolium cations occupy the axial positions and the O atoms of the four water molecules the equatorial positions. The two triazole ligands are parallel offset (with a distance of 1.38 A ° between their planes). In the anionic complex, the CoII ion is six-coordinated by two N and four O atoms of the two pyridine-2,6- dicarboxylate anions, exhibiting a slightly distorted octahedral coordination geometry in which the mean plane of the two pyridine-2,6-dicarboxylate anions are almost perpendicular to each other, making a dihedral angle of 85.87 (2). In the crystal, molecules are linked into a three-dimensional network via C—H O, C—H N, O—H O and N—H O hydrogen bonds.